Avelumab in patients with previously treated metastatic adrenocortical carcinoma: phase 1b results from the JAVELIN solid tumor trial - Christophe Le Tourneau; Christopher Hoimes; Corrine Zarwan; Deborah Jean Lee Wong; Sebastian Bauer; Rainer Claus; Martin Wermke; Hariharan Subramanian; Anja von Heydebreck; Vijay Kasturi; Vikram K. Chand; James L. Gulley (2018)
Background We assessed the efficacy and safety of avelumab, an anti-programmed death ligand 1 (PD-L1) antibody, in patients with previously treated metastatic adrenocortical carcinoma (mACC). Methods In this phase 1b expansion cohort, patients with mACC and prior platinum-based therapy received avelumab at 10 mg/kg intravenously every 2 weeks. Continuation of mitotane was permitted; however, mitotane levels during the study were not recorded. Tumor response was assessed by Response Evaluation Criteria In Solid Tumors v1.1. Results Fifty patients received avelumab and were followed for a median of 16.5 months. Prior treatment included ≥2 lines in 74.0%; mitotane was continued in 50.0%. The objective response rate (ORR) was 6.0% (95% CI, 1.3% to 16.5%; partial response in 3 patients). Twenty-one patients (42.0%) had stable disease as best response (disease control rate, 48.0%). Median progression-free survival was 2.6 months (95% CI, 1.4 to 4.0), median overall survival (OS) was 10.6 months (95% CI, 7.4 to 15.0), and the 1-year OS rate was 43.4% (95% CI, 27.9% to 57.9%). In evaluable patients with PD-L1+ (n = 12) or PD-L1− (n = 30) tumors (≥5% tumor cell cutoff), ORR was 16.7% vs 3.3% (P = .192). Treatment-related adverse events (TRAEs) occurred in 82.0%; the most common were nausea (20.0%), fatigue (18.0%), hypothyroidism (14.0%), and pyrexia (14.0%). Grade 3 TRAEs occurred in 16.0%; no grade 4 to 5 TRAEs occurred. Twelve patients (24.0%) had an immune-related TRAE of any grade, which were grade 3 in 2 patients (4.0%): adrenal insufficiency (n = 1), and pneumonitis (n = 1). Conclusions Avelumab showed clinical activity and a manageable safety profile in patients with platinum-treated mACC. Trial registration Clinicaltrials.gov NCT01772004; registered January 21, 2013.